PENGUATAN PRAKTIK MANAJEMEN SUMBERDAYA MANUSIA MELALUI EDUKASI PENYUSUNAN ANALISIS JABATAN DAN REKRUTMEN GURU - Tasnim Nikmatullah Realita; Made Iska Aprilita Wardhani; Anis Dwi Astanti; Novy Karmelita Indrawati (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
The competence and suitability of preschool teacher qualifications to their duties still face problems. This is due to the procedure for establishing job analysis descriptions and recruitment procedures that still do not meet statutory standards, as well as limited knowledge about these two things. This community service activity sought to close the knowledge gap through education and assistance in compiling job analysis descriptions and recruitment procedures, which were carried out at the Kyai Ageng Masrangi Islamic Kindergarten Education Institution, Sawojajar, Malang in October 2024. This activity was in collaboration with the foundation's management to explore the organization's goals, describe the positions and duties of the principal and the board of teachers in order to find out the teacher's workload. This community service activity produced descriptions of teacher positions, teacher job specifications and descriptions of recruitment procedures. For institutions, this activity provided benefits in the form of insight and skills in the early stages of HR management practices, thus efforts are made to implement HR management practices professionally. Therefore, it is recommended that institutions periodically and consistently evaluate the documents that have been prepared to be adjusted to the developments of the situation and needs.